Problemy związane z powstawaniem piany w procesie technologicznym produkcji cukru z buraków cukrowych - Janczar-Smuga, Małgorzata; Pietkiewicz, Jerzy Jan; Bogacz-Radomska, Ludmiła (Problems with Foam Occurence in the Beet Processing by the Sugar Production Biotechnology, 2008)
In this paper, the liquids foaming issues related to the beet processing by sugar production technology were defined. Main reasons of foam occurrence and problems with its persistence were presented. The foam occurrence in the beet processing by sugar production technology is an undesirable effect. Excessive foaming results from the technology defects and a reduced raw material quality. Reduction of foam formation rate and a foam elimination enhance the sugar performance and influence sugar quality. The foam occurrence issue by sugar production technology from sugar beet was reviewed in this paper, particularly in the following fields: general problems with liquids foaming and methods of foam formation rate reduction; analysis of factors which influence the foam formation rate and the intensity of foam occurrence in the sugar industry; activities towards reduction of the foam formation rate and intensity of foam occurrence, and methods of foam elimination as well. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 124-142